The Composition and Structure of Biofilms Developed by Propionibacterium acnes Isolated from Cardiac Pacemaker Devices - Okuda, Ken-ichi; Nagahori, Ryuichi; Yamada, Satomi; Sugimoto, Shinya; Sato, Chikara; Sato, Mari; Iwase, Tadayuki; Hashimoto, Kazuhiro; Mizunoe, Yoshimitsu (Frontiers in Microbiology, 2018)
The present study aimed to understand the biofilm formation mechanism of Propionibacterium acnes by analyzing the components and structure of the biofilms. P. acnes strains were isolated from the surface of explanted cardiac pacemaker devices that exhibited no clinical signs of infection. Culture tests using a simple stamp culture method (pressing pacemakers against the surface of agar plates) revealed frequent P. acnes colonization on the surface of cardiac pacemaker devices. P. acnes was isolated from 7/31 devices, and the isolates were categorized by multilocus sequence typing into five different sequence types (STs): ST4 (JK18.2), ST53 (JK17.1), ST69 (JK12.2 and JK13.1), ST124 (JK5.3), ST125 (JK6.2), and unknown ST (JK19.3). An in vitro biofilm formation assay using microtiter plates demonstrated that 5/7 isolates formed biofilms. Inhibitory effects of DNase I and proteinase K on biofilm formation varied among isolates. In contrast, dispersin B showed no inhibitory activity against all isolates. Three-dimensional live/dead imaging of P. acnes biofilms with different biochemical properties using confocal laser microscopy demonstrated different distributions and proportions of living and dead cells. Additionally, it was suggested that extracellular DNA plays a role in the formation of biofilms containing living cells. Ultrastructural analysis of P. acnes biofilms using a transmission electron microscope and atmospheric scanning electron microscope revealed leakage of cytoplasmic components along with cell lysis and fibrous structures of extracellular DNA connecting cells. In conclusion, the biochemical properties and structures of the biofilms differed among P. acnes isolates. These findings may provide clues for establishing countermeasures against biofilm-associated infection by P. acnes.